Water Quality Characteristics and Seasonal Changes in Wastewater Treatment in the Southern Hebei Region by Branch - Chao Qu; Weiyuan Cao; Kun Dong; Dunqiu Wang; Yi Yao (Toxics)
This study analyzed three years of data (2021–2024) from three wastewater treatment plants (WWTPs), namely D, X, and T, in the main urban area of Handan, a typical city in the southern Hebei region, and investigated the influent characteristics and impact of temperature on these wastewater treatment facilities. With 90% assurance, the overall influent conditions of the three WWTPs in this region were normal. However, Plant T operated more effectively with slightly lower BOD5/CODCr (B/C), organic carbon/total phosphorus (C/TP), and organic carbon/total nitrogen (C/TN) ratios in the influent. Plant D consistently met the Level A standard, Plant X essentially reached the Level A standard, while Plant T attained the Level 2 standard prior to its upgrade. Following the upgrade, Plant T also steadily met the Level A standard. The effluent from all plants was relatively stable, primarily influenced by the influent characteristics and slightly influenced by temperature, but without having a noticeable impact on the effluent quality.